1994
DOI: 10.3354/meps112107
|View full text |Cite
|
Sign up to set email alerts
|

Settlement and post-larvae behaviour of Mytitus galtoprovincialis: field and laboratory experiments

Abstract: Field sampling carried out in the Rfa de Vigo (NW Spain) from 1991 to 1993 showed that Mytdus galloprovincialis settle directly from the plankton onto substrates exposed to various environmental conditions: exposed rocky shore; protected rocky shore; exposed, raft mussel-culture area; and protected, raft mussel-culture area. For direct settlement, competent larvae may use a wide variety of substrates: filamentous nylon ropes; the byssus and intricately arranged material in the bottom of mussel beds; filamentou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…However, mussel spat are more abundant in finelybranched than coarsely-branched substrata, both natural and artificial (Alfaro & Jeffs 2002), and it has been argued that hydrodynamic processes alone can explain recruitment patterns on scales of > 3 cm (Bourget & Harvey 1998). Cáceres-Martínez et al (1994) suggest that settlement of Mytilus galloprovincialis is a passive process. Contact mucus threads produced by late pediveligers and post-larvae are more likely to snag filamentous surfaces so that algae trap settlers more efficiently than byssus threads, resulting in higher settlement on algae than on adult mussel beds (Lane et al 1985).…”
Section: Substratum Effectsmentioning
confidence: 99%
“…However, mussel spat are more abundant in finelybranched than coarsely-branched substrata, both natural and artificial (Alfaro & Jeffs 2002), and it has been argued that hydrodynamic processes alone can explain recruitment patterns on scales of > 3 cm (Bourget & Harvey 1998). Cáceres-Martínez et al (1994) suggest that settlement of Mytilus galloprovincialis is a passive process. Contact mucus threads produced by late pediveligers and post-larvae are more likely to snag filamentous surfaces so that algae trap settlers more efficiently than byssus threads, resulting in higher settlement on algae than on adult mussel beds (Lane et al 1985).…”
Section: Substratum Effectsmentioning
confidence: 99%
“…Most studies of patterns of settlement or recruitment of musse1.s have monitored artificial substrata (usually filamentous) and have found no evidence of colonization by mussels > 5 mm (e.g. De Rlok & Geelen 1958, King et al 1990, Caceres-Martinez et al 1994). In contrast, Paine (1974) observed that large Mytilus californianus (>3 cm) colonized plots of the natural substratum which had been cleared of mussels.…”
Section: Size Of Colonists and Temporal Pattern Of Colonizationmentioning
confidence: 99%
“…Caceres-Martinez et al, 1994;Dobretsov & Railkin, 1996). The observation that blue mussel spat 'preference' for filaments is more conspicuous in moving water than in the absence of currents seems to support this view (Eyster & Pechenik, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, however, larvae seem to directly settle into blue mussel beds (McGrath et al, 1988). Due to a secreted mucus thread, the larvae may be trapped by these filaments rather than actively 'choosing' them (Caceres-Martinez et al, 1994;Bourget & Harvey, 1998). A strong physical (passive) component in the process of primary settlement would explain why rates of settlement are enhanced by water movement (Eyster & Pechenik, 1987).…”
Section: Introductionmentioning
confidence: 99%